Psychometric Properties of the Turkish Version of Spondyloarthritis Knowledge Questionnaire: A Methodological Study - Öznur Erbay Dallı; Seda Pehlivan; Tuğba Ocak; Arzu Ceyhan; Yavuz Pehlivan (European Journal of Rheumatology, 2024)
Background: Information and education are recommended for patients with inflammatory arthritis including spondyloarthritis (SpA). However, there is no Turkish instrument available to measure the knowledge level of patients with SpA. The study aimed to translate the Spondyloarthritis Knowledge Questionnaire (SPAKE) into Turkish and investigate its validity and reliability.